2020
DOI: 10.1186/s12888-020-02485-4
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life as a protective factor against suicidal tendencies in Chinese University students

Abstract: Background: A substantial increase in rates of suicide worldwide, especially among late adolescents and young adults, has been observed. It is important to identify specific risk and protective factors for suicide-related behaviors among late adolescents and young adults. Identifying specific factors across the masses, not only in the Western, but also in the Asian context, helps researchers develop empirically informed intervention methods for the management of protective and risk factors of suicide.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 41 publications
(49 reference statements)
6
47
0
7
Order By: Relevance
“…Two waves of investigation were administered in the peak and remission periods during the COVID-19 outbreak in Chinese university students, with an interval of 4 months. Cross-lagged analysis indicated that university students who had reported higher level of meaning in life exhibited more emotional well-being, social well-being, and psychological well-being, which is consistent with the longstanding theorizing that meaning in life has a protective effect on mental health (Lew et al, 2020). Our results also showed that positive mental health helps to facilitate individuals' meaning in life.…”
Section: Discussionsupporting
confidence: 90%
“…Two waves of investigation were administered in the peak and remission periods during the COVID-19 outbreak in Chinese university students, with an interval of 4 months. Cross-lagged analysis indicated that university students who had reported higher level of meaning in life exhibited more emotional well-being, social well-being, and psychological well-being, which is consistent with the longstanding theorizing that meaning in life has a protective effect on mental health (Lew et al, 2020). Our results also showed that positive mental health helps to facilitate individuals' meaning in life.…”
Section: Discussionsupporting
confidence: 90%
“…Anxiety and depression comorbidities were identified as prominent mental health problems experienced by students (Lew et al, 2020; Mitsui et al, 2018; Russell et al, 2019; Taylor et al, 2020). These comorbidities were reported to be experienced as: feelings of helplessness and hopelessness (Akpinar Aslan et al, 2020; Bernanke et al, 2017; Reyes et al, 2015); loneliness/sense of disconnection (Chang et al, 2019); thwarted belongingness (Collins et al, 2018; Kwan et al, 2017; Lee et al, 2018); unbearable mental pain (Dhingra et al, 2019); sense of powerlessness in stressful events (de Albuquerque et al, 2019); psychological distress, emotional exhaustion, eating problems, and sleeping difficulties such as insomnia, nightmares, and sleep deprivation (Haghighi et al, 2018), fatigue (Rosiek et al, 2016); alexithymia; impulsivity; anhedonia; and low distress tolerance levels (Kratovic et al, 2020).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Often mental health problems resulted in maladaptive interpersonal behaviour, especially in the display of anger (Hollingsworth et al, 2018), affective dysregulation (Fang et al, 2019; Lew et al, 2020), and hostile reactions (Bruns & Letcher, 2018). Substance use was identified as a major cause of mental health problems further exacerbating student suicides.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations